Particle residence time measurement in a pressurized drop-tube reactor with radioactive tracer. (15th September 2019) - Rußig, Sascha; Gonzalez, Victor; Schurz, Martin; Krzack, Steffen; Kleeberg, Jörg; Guhl, Stefan; Meyer, Bernd
Highlights: Direct measurement of particle residence time in pressurized drop tube furnace. Investigation of influence of particle size, gas pressure, temperature, volume flow. Validation of sedimentation model for Reynolds numbers from 0.8 to 13.2. Experimental validation of limitation of Stokes' law to particle Reynolds numbers <1. Abstract: Particle residence time measurements were carried out in a pressurized drop-tube furnace (PDTF) using char particles marked with the isotope technetium-99 m. The effect of variations in the particle size (63–200 µm), gas temperature (673–1223 K), pressure (10–40 bar (g)) and superficial gas velocity (14–264 mm/s) was investigated, under reactive and inert atmosphere (CO2 ). The experimental method described in this work allowed the particle position to be determined experimentally as a function of time in a reactor that is otherwise not suited for the direct observation of the particles. This data can be correlated to the particle velocity and residence time. It was found that for the range of particle Reynolds numbers considered in this work (0.8–15.4), the experimental results can be described via the sedimentation velocity in combination with a drag force term based on the correlation by Haider and Levenspiel. An evaluation of the results revealed further insights into the correlation between the particle size distribution and the particle's residence time distribution, RTD.